Calculating the Surface Area of a Rolling Surface Using an Exact Integral (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Calculate The Area Of Rotary Surfaces Using A Definite Integral The Emphasis Is On How The Functionality Is Displayed. Because, Function May Give Obviously, Parametric And In Another System From Decart Coordinate System.